The Effect of Late Pregnancy Consumption of Date Fruit on Cervical Ripening in Nulliparous Women - Masoumeh Kordi; Fatemeh Aghaei Meybodi; Fatemeh Tara; Mohsen Nemati; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2014)
Background and Aim: Cervical ripening before the onset of labor is an important factor for the prediction of delivery mode, and is directly associated with vaginal delivery. The search for a safe, inexpensive, and easy method of cervical ripening is of great significance. Few studies have focused on the effect of date fruit on uterine contractions and cervical ripening. Therefore, the purpose of this study was to determine the effect of late pregnancy consumption of date fruit on cervical ripening in nulliparous women. Methods: This randomized clinical trial was performed on 210 women with a singleton pregnancy, cephalic presentation, and gestational age of 37-38 weeks. The study was conducted at Omolbanin Hospital, Mashhad, Iran in 2013. The subjects were randomly assigned into two groups of 105 women (experimental and control groups). Since the 37th week of gestation, the experimental group consumed date fruit (70 to 75 gr per day) until the onset of labor pain, and the control group received routine care. Data were collected using demographic questionnaires, fetal movement record form, and the checklist related to daily consumption of date fruit. Data analysis was performed using SPSS version 14, and Chi-square, t student, and Mann-Whitney test. P-value less than 0.05 was considered statistically significant. Results: The mean Bishop score at admission was higher in the experimental group (7.67 ± 2.28), compared to the control group (5.12 ± 2.77) (P